Experimental and MD simulation study on the physical and mechanical properties of organically modified montmorillonite clay and compatibilized linear low density polyethylene nanocomposites. Issue 6 (5th October 2017) - Yildirim, Erol; Yurtsever, Mine; Eriman, Bülent; Uyanik, Nurseli
ABSTRACT: Understanding the interfacial interactions plays a key role in controlling mechanical and physical properties of polymer/clay nanocomposites (PCNs). In this work, the surface interactions between constituents of experimentally prepared PCNs which are the pristine linear low density polyethylene (PE) chains, PE compatibilizers, montmorillonite clay surface layer, and surfactants were studied quantitatively by employing molecular dynamics simulation technique. The interaction energy between the polymer and the clay was found to be inversely proportional with the volume of the surfactant which decreases the electrostatic interactions between the compatibilizer and the hydrophilic clay surface. However, the van der Waals (vdW) interactions between alkyl tails of surfactants and the PE chains increase with the tail length of the surfactants. The most attractive interaction was between the surfactant's head group and the clay surface. We showed that there existed fine balance between the electrostatic and vdW type forces on the stability and the enhanced properties of the PE–organoclay nanocomposites. Calculated interaction energies were then correlated to the experimentally measured mechanical properties. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45817. Abstract :